Supporting Premature Infants' Oral Feeding in the NICU-A Qualitative Study of Nurses' Perspectives - Evalotte Mörelius; Charlotte Sahlén Helmer; Maria Hellgren; Siw Alehagen (MDPI AG, 2021)
One major task in the neonatal intensive care unit (NICU) involves ensuring adequate nutrition and supporting the provision of human milk. The aim of this study was to explore nurses' experiences of the oral feeding process in the NICU when the infant is born extremely or very preterm. We used a qualitative inductive approach. Nine nurses from three family-centered NICUs were interviewed face-to-face. The interviews were transcribed verbatim and analyzed using content analysis. Five sub-categories and two generic categories formed the main category: 'A complex and long-lasting collaboration.' The nurses wished to contribute to the parents' understanding of the feeding process and their own role as parents in this process. The nurses' intention was to guide and support parents to be autonomous in this process. They saw the family as a team in which the preterm infant was the leader whose needs and development directed the feeding and the parents' actions in this process. Written and verbal communication, seeing all family members as important members of a team and early identification of the most vulnerable families to direct the emotional and practical feeding support accordingly can strengthen the feeding process in the NICU.